2021
DOI: 10.1111/jfpp.15346
|View full text |Cite
|
Sign up to set email alerts
|

Fish and garlic oils hybridized microcapsules: Fortification in functional bread

Abstract: Hybridized microcapsules (MCs) containing fish oil (FO), garlic oil (GO), and their combination (FO + GO) were prepared and the effect of their fortification in bread was studied. Functional bread fortified with 5% hybrid MCs reported increased TBARS, but remained acceptable range over 7 days storage period at 4 ± 1°C (<25% RH) in LDPE (thickness: 0.05 mm) packaging. Textural analysis of bread samples demonstrated significantly (p < .001) increased hardness without changes in the cohesiveness and springiness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Indeed, the encapsulation of oils can inhibit or delay their oxidation and mask negative flavors and unpleasant tastes [31]. In addition, as reported by several authors, the encapsulation of oils could protect them in the gastrointestinal tract without altering their chemical characteristics [32,33]. Moreover, the addition of encapsulated oils in bread could affect most of the technological and sensory properties, such as bread volume, texture, fatty acids bioavailability, the bread's oxidative stability, and sensory properties (Table 3).…”
Section: Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, the encapsulation of oils can inhibit or delay their oxidation and mask negative flavors and unpleasant tastes [31]. In addition, as reported by several authors, the encapsulation of oils could protect them in the gastrointestinal tract without altering their chemical characteristics [32,33]. Moreover, the addition of encapsulated oils in bread could affect most of the technological and sensory properties, such as bread volume, texture, fatty acids bioavailability, the bread's oxidative stability, and sensory properties (Table 3).…”
Section: Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 94%
“…In addition to the coating polymers, the nature of the core had a significant impact on the oxidation of the fortified bread. Regarding this, Sridhar et al [33] and Kairam et al [36] demonstrated a synergistic effect between the mixtures of oils selected as the core material (garlic oil combined with fish or flaxseed oil) in reducing oil oxidation throughout the storage period. In these studies, the secondary oxidation products during a week of storage were lower in bread fortified with the oils blend (0.32 µmol of malonaldehyde/g at day 7 with fish and garlic oil as compared with 0.48 µmol of malonaldehyde/g at day 7 for bread fortified with only fish oil) [33].…”
Section: Bread Oxidative Stabilitymentioning
confidence: 99%
“…When studies on bread, especially in recent years, are examined, it is seen that different issues are examined. The main ones are a) the effects of different microorganisms on bread (Hajinia et al, 2020;Cizeikiene et al, 2020;Bockwoldt et al, 2021), b) bread production with low glycemic index (Sridhar et al, 2021) and low FODMAP (Menezes et al, 2021), c) gluten-free bread production (Jagelaviciute & Cizeikiene, 2021;Maidana et al, 2020), d) use of different ingredients as flour and their effect on bread (Jagelaviciute & Cizeikiene, 2021), and e) functional bread production as the common point of these studies. Jagelaviciute & Cizeikiene (2021) examined the effect of unconventional sourdough made with quinoa, chia, and hemp flour on the quality and acceptability of dough and gluten-free corn / rice bread.…”
Section: Word Evolution Of Bread and Sourdough Research Titlesmentioning
confidence: 99%
“…Current research also emphasizes how the perception of bread consumption is changing. Many studies have also focused on the possibility of adding functional ingredients to improve and increase the original nutritional value of bread (Althwab et al, 2021;Weng et al, 2021;Sridhar et al, 2021). According to Althwap et al (2021), effects of incorporation of Locusta migratoria (LM) powder at different levels (0, 1, 2, 3, 4 and 5%) on nutritional, qualitative and sensory properties of baked breads were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Fortification of food products with fish oil by encapsulation technique can be a way to increase its availability and improve consumer health. Various studies reported that used encapsulated fish oil and omega-3 fatty acids in food products such as bread ( Ojagh and Hasani, 2018 , Sridhar et al, 2021 ), chicken nuggets ( Pourashouri, Shabanpour, Heydari, & Raeisi, 2021 ), sausage ( Pourashouri, Shabanpour, Kordjazi, & Jamshidi, 2020 ), mayonnaise ( Miguel et al, 2019 ), juice ( Sridhar, Sharma, Choudhary, Dikkala, & Narsaiah, 2021 ), and snacks ( Álvarez and Lamas 2021 ). Dairy products are good candidates for omega-3 fortification because of their high amount of consumption and stored under refrigerated conditions ( Zhong et al, 2018 , Hamed et al, 2019 , Mieehsanpazir and Asadi 2021, Zakipour Rahimabadi 2021).…”
Section: Introductionmentioning
confidence: 99%